Evaluation of the Back-in-Action test Battery In Uninjured High School American Football Players - Marcel Rohde; Alina Ruhlemann; Andre Busch; Ulrich Grunwald; Marcus Jaeger; Constantin Mayer (International Journal of Sports Physical Therapy)
# Background